Geographic information system-allocation model for forest path: a case study in Ayer Hitam Forest Reserve, Malaysia - Ismail, Mohd Hasmadi; Zaki, Pakhriazad Hassan; Mohamad, F. S. (Science Publications, 2010)
Problem statement: Forest road planning requires a host of information, particularly the availability of spatial and non-spatial data. The requirement of a planning system or tools to gather, integrate and manipulate all data is essential. The ability of Geographic Information System (GIS) to integrate such massive information and develop a spatial model of earth features will lead to time and cost reduction and allows analysis of spatial problems more effective than the traditional method. Approach: The objective of this study was to test the potential of GIS in modeling forest road allocation in Ayer Hitam Forest Reserve (AHFR), Selangor, Malaysia. This study is also to compare a road profile (new path) generated from GIS approach (new path) with existing forest road and allocates the best road path for compartment 2 and 14. Data from digital topographic map was used to generate slope class, elevation class, direction and distance. New road paths were determined using spatial analyst. Several module or technique that used were cost weight, reclassify, raster calculator and shortest path modeling. Results: Results showed that road path generated from GIS technique was shorter and avoid more unnecessary slope and elevation. Road profiles such as elevation, slope and length were analyzed and discussed. Conclusion: The result clearly revealed that GIS has strength and played a vital role in modeling forest road allocation effectively and reduced time consuming.